Peran Emosi Positif sebagai Mediator Stimulus Lingkungan Toko dan Faktor Sosial terhadap Impulse Buying Tendency pada Matahari Departement Store Kota Ambon - Hetharie, Jondry Adrin (Jurnal Aplikasi Manajemen, 2012)
Reality in condition of kota Ambon post-horizontal conflict and along with improvement in security situation also economy restoration has been conducted by the government, it is proved in economy growth in kota Ambon reaching 5% in 2008 compared with 0% in 1999. These conditions has encourage business activities in general, affecting commercial growth, in this case the growth of modern markets which is vying in attracting as many customers they can get to shops and how to deliver best service towardconsumers. This study has the objective to test stimulus which is given from store's environment and store's social factor toward impulsive buying tendency mediated by positive emotion of consumers at Mataharidepartement store in Kota Ambon. This study is an explanatory research. Population of this study is consumers who shops in Matahari Department Store in Kota Ambon. With respondent for 128 people, samplingdetermination is using purposive sampling method. Data analysis technique in this study is using path analysis. Result of the analysis showed that there are direct effects from physical environment and social aspect of the store toward consumer's positive emotion and toward impulsive buying tendency. Result of this study also revealed that there are direct effects of consumer's positive emotion toward impulsive buying tendency and indirect effects of store's environment stimulus and store's social factor toward impulsivebuying tendency mediated by consumer's positive emotion.